Recruitment of HP1β to UVA-induced DNA lesions is independent of radiation-induced changes in A-type lamins - Sehnalová, Petra; Legartová, Soňa; Cmarko, Dušan; Kozubek, Stanislav; Bártová, Eva (Biology of the cell, 2014)
BACKGROUND INFORMATION: The optimal repair of DNA lesions is fundamental for physiological processes. We asked whether the recruitment of HP1β, 53BP1 and BMI1 proteins to ultraviolet (UVA)-induced DNA lesions requires functional A-type lamins. RESULTS: We found that UVA irradiation of nuclear lamina abolished the fluorescence of mCherry-tagged A-type lamins and destroyed the nuclear lamina as also observed by electron microscopy studies. Similarly, an absence of endogenous A- and B-type lamins was found in irradiated regions by UVA. However, irradiation did not affect the recruitment of HP1β, 53BP1 and BMI1 to DNA lesions. The UVA-induced shrinkage of the nuclear lamina, which anchors chromatin, explains why UVA-micro-irradiated chromatin is relaxed. Conversely, additional experiments with γ-irradiation showed that the nuclear lamina remained intact and the genome-wide level of HP1β was stable. Fluorescence intensity of HP1β and BMI1 in UVA-induced DNA lesions and level of HP1β after γ-irradiation were unaffected by deficiency in A-type lamins, whereas those parameters of 53BP1 were changed. CONCLUSIONS: We conclude that only the 53BP1 status in DNA lesions, induced by UVA or γ-rays, is affected by A-type lamin deficiency, which was not observed for heterochromatin-related proteins HP1β and BMI1.
Keywords: Protein mobility; PRC1; buňky 3T3; DNA-Binding Proteins; 53BP1; chromozomální proteiny, nehistonové; DNA damage; DNA vazebné proteiny; Polycomb Repressive Complex 1; HP1; Tumor Suppressor p53-Binding Protein 1; zvířata; myši; ultrafialové záření; protoonkogenní proteiny; Mice; Chromatin; DNA; Chromosomal Proteins, Non-Histone; 3T3 Cells; Lamin Type A; Lamins; Proto-Oncogene Proteins; poškození DNA; DNA Damage; Ultraviolet Rays; Animals; lamin typ A